Spectrophotometry of Winkler and White's official methods for the determination of hydroxymethylfurfural in bee honey - Maeda, Isabel Cabral [UNESP]; Sampaio, Aryele Nunes Da Cruz Encide [UNESP]; Flores Caron, Evelyn Fernanda [UNESP]; Nardy, José Fernando [UNESP]; Oliveira, Sarah Cristina De [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Martins, Otávio Augusto [UNESP] (Instituto de Tecnologia de Alimentos - ITAL, 2023)
The determination of hydroxymethylfurfural (HMF) in bee honey is performed by the spectrophotometric methods Winkler's and White's. The Winkler method reads the absorbances in the visible region of the spectrum, and the White method measures in the ultraviolet (UV) and visible regions of the spectrum. This study aims to compare the spectrophotometric methodologies of White and Winkler to the determination of HMF in bee honey. For the study, it was used a UV-visible spectrophotometer, 10 mm optical path quartz cuvettes, and ten bee honey samples of different flowering. Absorbances at 550 nm were analyzed by the Winkler method; absorbances at 284 nm and 336 nm in the White method; and a comparison of HMF concentration (mg/kg) was carried out between the methods. The results showed significant differences (p<0.05) in HMF concentration determined by both methods. The main conclusion is that the Winkler method presents higher HMF values than the White method.

There are no significant differences in the absorbance readings in the evaluated methodsHMF values were different between the White and Winkler methodsThe Winkler method presents higher HMF values than the White method
Keywords: Absorbance; Bees; Comparison; HMF; Physicochemical; Spectrophotometer